2004
DOI: 10.1128/jb.186.4.1129-1135.2004
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Multiple CotC Forms into the Bacillus subtilis Spore Coat

Abstract: We report evidence that the CotC polypeptide, a previously identified component of the Bacillus subtilis spore coat, is assembled into at least four distinct forms. Two of these, having molecular masses of 12 and 21 kDa, appeared 8 h after the onset of sporulation and were probably assembled on the forming spore immediately after their synthesis, since no accumulation of either of them was detected in the mother cell compartment, where their synthesis occurs. The other two components, 12.5 and 30 kDa, were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 30 publications
8
92
0
1
Order By: Relevance
“…To visualize actual spore formation within the colonies, we constructed a full translational fusion of the gene encoding the abundant spore coat protein CotC (21) to the gfp gene under control of its own promoter. A C-terminal GFP fusion was constructed instead of an N-terminal fusion to avoid possible loss of the GFP marker by removal of the N-terminal part of the protein due to posttranslational processing (25). Correct timing and localization of the P cotC -CotC-GFP fusion to the forespore were confirmed by single-cell fluorescence microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To visualize actual spore formation within the colonies, we constructed a full translational fusion of the gene encoding the abundant spore coat protein CotC (21) to the gfp gene under control of its own promoter. A C-terminal GFP fusion was constructed instead of an N-terminal fusion to avoid possible loss of the GFP marker by removal of the N-terminal part of the protein due to posttranslational processing (25). Correct timing and localization of the P cotC -CotC-GFP fusion to the forespore were confirmed by single-cell fluorescence microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, about 30% of the total spore coat protein is refractory to extraction, forming an insoluble highly cross-linked fraction (5,10,30). Several coat proteins appear to be cross-linked, and the available evidence suggests that both reversible and irreversible cross-links occur within the coat (5,10,11,12,14,20,21,42). In a classical study, Pandey and Aronson (30) have suggested the existence of o,o-dityrosine cross-links in purified coat material, an observation confirmed by more recent work (5).…”
mentioning
confidence: 78%
“…The B. subtilis spore coat is composed of several distinct layers and contains Ն30 proteins, almost all of which are spore-specific gene products (5)(6)(7)(8)(9)(10)(11)(12). There is extensive cross-linking of a number of proteins in the coats, at least in part by a transglutaminase and perhaps by the formation of dityrosine cross-links as well (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%